2010
DOI: 10.1097/jto.0b013e3181e2f624
|View full text |Cite
|
Sign up to set email alerts
|

Korean Ethnicity as Compared with White Ethnicity Is an Independent Favorable Prognostic Factor for Overall Survival in Non-small Cell Lung Cancer before and after the Oral Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor Era

Abstract: These results suggest that Korean ethnicity compared with US white ethnicity is an independent favorable prognostic factor for OS in NSCLC. In addition, greater survival benefit among Korean patients with NSCLC was noted in the postepidermal growth factor receptor tyrosine kinase inhibitor era (2002 and after) compared with US white ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 21 publications
1
36
1
Order By: Relevance
“…In addition, they used a semi-quantitative histological score, which was obtained by multiplying the percentage of reactive cells by the corresponding immunostaining intensity, as a continuous variable to evaluate immunohistochemical findings, whereas we used a binary variable, In our study, the proportion of never smokers was 24 %, which is much higher than that reported in non-Asian countries and contradicts the well-established strict relation between SCLC and cigarette smoking [14,15]. The prevalence of nonsmoking-related lung cancer, regardless of histological type, is known to be higher among Asian patients including Koreans than in non-Asian patients, and this could be explained by ethnic differences [15][16][17]. In addition, 22 (79 %) of 28 never smokers included in this study were female.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition, they used a semi-quantitative histological score, which was obtained by multiplying the percentage of reactive cells by the corresponding immunostaining intensity, as a continuous variable to evaluate immunohistochemical findings, whereas we used a binary variable, In our study, the proportion of never smokers was 24 %, which is much higher than that reported in non-Asian countries and contradicts the well-established strict relation between SCLC and cigarette smoking [14,15]. The prevalence of nonsmoking-related lung cancer, regardless of histological type, is known to be higher among Asian patients including Koreans than in non-Asian patients, and this could be explained by ethnic differences [15][16][17]. In addition, 22 (79 %) of 28 never smokers included in this study were female.…”
Section: Discussioncontrasting
confidence: 80%
“…Compared with patients in the Asian phase-III gefitinib trials, [14][15][16] patients in the EURTAC trial 33 had the highest median age, the highest proportion with a worse performance status, and the highest proportion with stage IV disease, apart from using a Caucasian patient population which in itself was an important prognostic factor. [34][35][36] Thus, according to these prognostic patient characteristics, the only phase-III trial performed in Caucasian patients (EURTAC) was not comparable to any other phase-III trial and hence warranted assessment separately from the Asian evidence. Notably, this was our rationale for basing our assessment for the Hong Kong health care setting on the available Asian evidence only.…”
Section: Discussionmentioning
confidence: 99%
“…prognosis among patients with non-small cell lung cancer. 19 Taking this idea a step further, we suggest that for each race and cancer previously listed, there are likely numerous unidentified genetic and molecular differences of oncologic significance that can be exploited for therapeutic gain in the future.…”
Section: Discussionmentioning
confidence: 99%